Heat-induced interactions of hemp protein particles formed by microfluidisation with β-lactoglobulin - Ma S; Acevedo-Fani A; Ye A; Singh H (Elsevier Ltd, 2024)
This study explored the effect of microfluidization on the dispersibility of hempseed protein (HP) and the interactions of microfluidised HP particles with β-lactoglobulin (β-lg) after heat treatment. Microfluidization increased the dispersible protein fraction from 10% (non-microfluidised) to a maximum of 58% (200 MPa, 6 passes) in HP dispersions. Dispersible HP particles were within the micro-sized range (d4,3 ≤ 2 μm) after microfluidization. Heat treatment (95 °C, 10–60 min) of HP particles with β-lactoglobulin (β-lg) induced protein association by sulphydryl-disulphide exchange reactions; β-lg association with HP particles initiated within the first 20 min. Additionally, the particle size (d4,3) values of co-heated HP particles with β-lg were significantly smaller than those found in HP particle dispersions heated alone, results that were in line with microscopy analysis. This suggests that β-lg could have restricted HP particle aggregation. In conclusion, combining microfluidization and heat treatment could offer a venue to modify the physical properties of plant/milk protein mixtures.
Keywords: Hempseed protein; β-lactoglobulin; Protein-protein interactions; Microparticulation; Dairy alternatives; Hybrid protein